Yo-kai watch. 8, A boohoo battle - Konishi, Noriyuki; Sitterson, Aubrey (VIZ Media, LLC, 2018)
Ordinary elementary school student Nathan Adams continues to use his Yokai Watch to make friends with or investigate spiritual yokai disturbances, together with his friend and butler the yo-kai Whisper, the cat yo-kai Jibanyan, the rabbit-esque yo-kai Usapyon, and fifth grader Hailey Anne Thomas, the self-proclaimed superfan of aliens and sailor cuties.